62 Groups often under-served by research are keen to participate, regardless of prognosis, performance status and socio-economic position. A Multi-Centre Cohort study of 100 Specialist Palliative Care Inpatients. (14th March 2023) - Atkinson, Kate; Spriggs, Helena; Dewhurst, Felicity; Wakefield, Donna; Elverson, Joanna; McConnell, Robert; Frew, Katherine
Abstract : Objectives: Palliative care services need to embrace research to guide service development and effective symptom management. Healthcare professionals often feel research is too burdensome for patients who have poor performance status or are near the end-of-life. In addition to gatekeeping from clinicians, many studies explicitly exclude these groups from participating. We aimed to identify whether specialist palliative care inpatients would wish to take part in research and whether preference varies according to study design, demographics, diagnosis, performance status and prognosis. Methods: 100 inpatients in two NHS Specialist Palliative Care Units and one independent Hospice in the Northeast of England completed a short questionnaire about preferences for involvement in research. Results: 92% of participants stated they were interested in being involved in research. This was mostly unaffected by age, diagnosis, prognosis, performance status and socioeconomic status. Three quarters of the patients surveyed were within the last three months of life. Simple questions or interviews were the preferred methodology, whereas only half of patients would want further investigations or additional medications and fewer still wanted to participate in online activities, life-style change or group activities. Conclusions: Palliative care inpatients welcome the opportunity to be involved in research and should not be excluded on the grounds of advanced disease, poor prognosis and low performance status. Research into end-of-life care should incorporate study designs that would be acceptable and tolerable to patients with advanced disease, rather than exclude them.